2021
DOI: 10.1016/j.heliyon.2021.e07842
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and commitment therapy for individuals having attention deficit hyperactivity disorder (ADHD): A scoping review

Abstract: Objectives Acceptance and commitment therapy (ACT) has accumulated increasing evidence-base for a broad range of mental health issues. Considering that ACT encourages broad and flexible patterns of behaviour and neutralizes the pervasive psychological processes proposed to be caused by most individuals' distress, such a modality may be effective for ADHD. This review aimed to give a synthesis of the studies, so far, focusing on the usefulness of ACT approaches among individuals having ADHD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…The results demonstrated the ACT's effectiveness in enhancing emotion regulation strategies, boosting academic performance, and mitigating behavioral symptoms in children with ADHD. This finding is consistent with those of Munawar et al (24). Sánchez et al (10) revealed that hyperactive children struggle with the cognitive processing of emotional information and regulating their emotions.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results demonstrated the ACT's effectiveness in enhancing emotion regulation strategies, boosting academic performance, and mitigating behavioral symptoms in children with ADHD. This finding is consistent with those of Munawar et al (24). Sánchez et al (10) revealed that hyperactive children struggle with the cognitive processing of emotional information and regulating their emotions.…”
Section: Discussionsupporting
confidence: 91%
“…5 themselves, worries about relationships with others, and inappropriate social performance (12). When discussing the impact of ACT-based parenting training on ADHD children's emotion regulation, behavioral symptoms, and academic performance, it is worth noting that ACT interventions incorporate cognitive defusing, acceptance of unpleasant thoughts and feelings, and mindfulness skills (24). These parameters improved parents' psychological flexibility and their ability to respond more adaptively to their child's misbehavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of medicalizing the child's behavior through a diagnosis of the brain, focus is on giving support and help to the parents, which serves as a treatment also for the child. In accordance with this view, psychotherapeutic techniques ( 25 , 76 78 ) could be alternatives to the current, often first-of-choice, central-stimulant medication. Within a psychotherapeutic framework, children diagnosed with ADHD can receive unique attention allowing them to communicate what they perceive as most disturbing in their life.…”
Section: Discussionmentioning
confidence: 93%